IMPLEMENTASI PERATURAN PEMERINTAH NOMOR 30 TAHUN 2019 TENTANG PENILAIAN KINERJA PEGAWAI NEGERI SIPIL PADA DINAS SOSIAL KOTA BENGKULU - Tambun Saribu, Gracya Rotua; Hakim, Kahar; Yogopriyatno, Jatmiko (SENGKUNI Journal (Social Science and Humanities Studies), 2024)
The aim of this research is to find out and describe the process of implementing Government Regulation Number 30 of 2019 concerning Performance Assessment of Civil Servants at the Bengkulu City Social Service. To describe clearly and in detail the data obtained from this research, the researcher used a descriptive qualitative research approach. Based on the results of this research, it can be concluded that the implementation of Government Regulation Number 30 of 2019 concerning Performance Assessment of Civil Servants at the Bengkulu City Social Service has been carried out but has not gone well, this is proven by the socialization that has been carried out via social media, namely the WhatsApp application, but has not yet been implemented. effectiveness can be seen from the lack of understanding of civil servants in filling out the SKP. So socialization must be carried out directly to explain again how to fill in and the contents of these regulations. The implementation has not gone well, because many civil servants have problems filling out the SKP so that civil servants have to ask the Head of Civil Service Subdivision even though the person concerned doesn't really understand. This causes many errors to occur when the files are collected which cause the files to be returned for repair. Monitoring has been going well, as evidenced by the discovery of obstacles in filling out the SKP. Evaluation, where there are civil servants who state that no evaluation has been carried out at the Social Service. This proves that the concept of evaluation activities is still unclear, thus making civil servants confused about whether the activities are being evaluated or not.